1998
DOI: 10.1007/s001670050083
|View full text |Cite
|
Sign up to set email alerts
|

Ligament force and joint motion in the intact ankle: a cadaveric study

Abstract: The aims of this study were to measure the forces in the anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL) and the motion in the tibiotalar and subtalar joints during simulated weight-bearing in eight cadaver ankle specimens. An MTS test machine was used to apply compressive loads to specimens held in a specially designed testing apparatus in which the ankle position (dorsiflexion-plantarflexion and supination-pronation) could be varied in a controlled manner. The forces in the ATFL and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 24 publications
10
71
0
Order By: Relevance
“…The primary ligamentous restraint to an inversion moment in a plantarflexed position is the anterior talofibular ligament (Bahr et al, 1998). In line with this, inversion sprains have traditionally been described as resulting from a combination of inversion and plantar flexion (Andersen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The primary ligamentous restraint to an inversion moment in a plantarflexed position is the anterior talofibular ligament (Bahr et al, 1998). In line with this, inversion sprains have traditionally been described as resulting from a combination of inversion and plantar flexion (Andersen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Bahr et al 3 indicated that variability in ligament orientation could be a source of variability in the results of talocrural joint displacement testing in cadaver ankles; however, Taser et al 34 found that the anatomical orientation of the ATFL between the origin and insertion is not widely variable, despite variability in ATFL lengths among studies. These factors, along with differences in injury history, may account for the wide variability observed within each group on these laxity measures.…”
Section: Stress Ultrasoundmentioning
confidence: 99%
“…Within the functional range of motion, the ligament provides little resistance to motion; however, as the ankle approaches the end of its range of motion, the ligament reaches high strains and greatly increases its resistance to further motion, providing passive ankle support. 4,8,25,26,31 The second disadvantage of conventional athletic tape as compared to natural ligament is that the former looses much of its support characteristics within a relative short time after the initiation of exercise. In the present study, conducted on 11 athletes, we found that conventional athletic tape reduced ankle flexibility in inversion by an average of 33% initially but by only 15% following a 30-minute exercise session, a 55% loss of support.…”
mentioning
confidence: 99%